Validation of the fatigue severity scale in a Swiss cohort - Valko, Philipp O; Bassetti, Claudio L; Bloch, Konrad E; Held, Ulrike; Baumann, Christian R (Sleep (New York, N.Y.), 2008)
Fatigue is highly prevalent and has a negative impact on quality of life and performance in a variety of disorders. The 9-item Fatigue Severity Scale (FSS) is one of the most commonly used self-report questionnaires to measure fatigue, but has only been validated in small sample-sized studies and in single disorders. To validate the FSS in healthy subjects and different disorders known to be commonly associated with fatigue. The FSS was administered to 454 healthy subjects, 188 patients with multiple sclerosis (MS), 235 patients with recent ischemic stroke, and 429 patients with sleep-wake disorders including narcolepsy with cataplexy (n=22), restless legs syndrome (RLS) (n=79), sleep apnea (n=108), insomnia (n=62), parasomnia (n=25), excessive daytime sleepiness/hypersomnia of other origin (n=84, and other sleep-wake disorders (n=49. FSS scores were 4.66 +/- 1.64 (mean +/- SD) in patients with MS, 3.90 +/- 1.85 in patients after ischemic stroke, and 4.34 +/- 1.64 in patients with sleep-wake disorders. Compared to patients, values were significantly lower in healthy subjects (3.00 +/- 1.08, P < 0.01). Scores did not correlate with gender, age, or education. Item analysis showed an excellent internal consistency and reliability (Cronbach alpha = 0.93). Test-retest variability was assessed in 104 healthy subjects, showing stable values over time (2.94 +/- 0.90 vs. 2.90 +/- 0.74; P = 0.27). This first validation of a fatigue scale in a large sample size demonstrates that the FSS is a simple and reliable instrument to assess and quantify fatigue for clinical and research purposes.